Implementation of Android-Based E-Raso Media to Enhance Students’ Environmental Care Character in Bima - Haryadi, Didit; Zulkifli, Zulkifli; Sumardin, Sumardin; Ahmadin, Ahmadin; Komalasari, Desy Ningsih (Journal of Educational Sciences, 2025)
Ideally junior high school students should demonstrate awareness and concrete practices such as reducing plastic waste, maintaining cleanliness, reusing waste materials, and actively participating in greening activitiesThe objectives of this study are: (1) to determine the effect of using the Android-based E-Raso media to enhance students’ environmental care character, and (2) to identify the factors that influence students’ environmental care character. This research employs a quantitative approach with a pre-experimental method and a One-Group Pretest-Posttest design. The study was conducted at SMPN 1 Kota Bima with a sample of 33 students. Data collection techniques included both test and non-test methods. The test instrument consisted of pretest and posttest questions, while the non-test instrument consisted of documentation. The results showed a significant increase in the average score, rising from 59.50% on the pretest to 86.83% on the posttest. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05), confirming a significant effect of using the Android-based E-Raso media in improving students’ environmental care character. Therefore, the Android-based E-Raso media proved to be influential and effective, serving as one of the supporting factors for enhancing this ability.